Childhood Maltreatment and Adolescents' Aggression: A Moderated Mediation Model of Callous-Unemotional Traits and Friendship Quality. (November 2022) - Li, Wenqing; Yang, Jiping; Gao, Ling; Wang, Xingchao
A growing body of research has documented that childhood maltreatment is associated with increased risk of child aggression. However, little is known about the mediating and moderating mechanisms underlying the relationships between childhood maltreatment and reactive and proactive functions of aggression. Therefore, the present study examined whether callous-unemotional traits mediated the relationships between childhood maltreatment and two subtypes of aggression and whether these mediating processes were moderated by friendship quality. A cross-sectional study was conducted among 2407 adolescents between 11 and 16 years ( M age = 12.75, SD = .58) in Shanxi province, China. Participants filled out questionnaires regarding childhood maltreatment, callous-unemotional traits, aggression, and friendship quality. The results indicated that childhood maltreatment was significantly and positively associated with proactive and reactive aggression, and these relationships were partially mediated by callous-unemotional traits after controlling for demographic variables. Friendship quality moderated the relationship between childhood maltreatment and proactive aggression as well as callous-unemotional traits and proactive aggression. These relationships became weaker for adolescents with high levels of friendship quality. Friendship quality did not moderate the effects of childhood maltreatment and callous-unemotional traits on reactive aggression.